Win from within build organizational culture for competitive advantage - Heskett, James L. 1933- (Columbia University Press, 2022)
Win from Within offers a playbook for developing and deploying organizational culture that enables outsized results. It is a groundbreaking demonstration of culture's role as a foundation for strategic success-and its measurable impact on the bottom line.
Keywords: Corporate Identity; Unternehmenskultur